The Notion of Phoenicia in the Roman Period - Głogowski, Piotr (Polskie Towarzystwo Filologiczne, 2018)
The aim of this paper is to display the evolution of the term Phoenicia in the Roman times (64 BCE–636 CE) by focusing on the most important issues regarding this problem, i.e. the geographical extension of the notion of Phoenicia, the transition from its geographical meaning into its the administrative one and the role the establishment of the Roman province of Syria Phoenice (194 CE) played in this process. The paper shows that the concept of Phoenicia in Roman times was influenced by the Hellenistic term Syria and Phoenicia. The provincial identity of the Phoenicians also seems to have been a product of the extension of the notion of Phoenicia further inland and some Eastern communities, which were never before thought to be Phoenician, could now share this identity as a means of integration into the Graeco-Roman world. The problem of the notion of Phoenicia in the Roman period seems to be a neglected topic and the current paper is an attempt to fill the gap in that field
Keywords: Phoenicia (64 BCE–636 CE)